Physiological characteristics of young (9-12 years) and adolescent (=13 years) rhythmic, acrobatic, and artistic female gymnasts - Steinberg, N.; Elbaz, L.; Dar, G.; Nemet, D.; Eliakim, A. (Sports Health: A Multidisciplinary Approach, 2025)
Background: Elite gymnasts are exposed to high levels of physical stress, during both childhood and adolescence, with significantly late maturation and high injury prevalence. Here, we compare the physiological characteristics of female gymnasts in 2 age groups: young (9-12 years) and adolescent (=13 years) in 3 disciplines of competitive gymnastics.